2010
DOI: 10.5650/jos.59.41
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Body Weight-loss Promoting Oil Prepared with Vegetable Protein

Abstract: It has been reported that oil thermally processed with wheat gluten (gluten oil) exhibited safe weight-loss promoting effects in animal experiments. However, as the oil has a high color index, and its chemical properties and smell differ from those of fresh oil, it is uncertain if the oil will find market acceptance. In order to resolve the issue, frying oil was heated with soybean protein under reduced pressure (soybean protein oil), resulting in a product with an appearance, chemical properties and smell com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…It was reported that oil heated with soybean protein under reduced pressure, followed by fi ltration of the protein soy oil , accelerated gastrointestinal tract content transfer 2 . Furthermore, the content in the colon was actively excreted, ending up with remarkable weight-loss even though amounts ingested were constant 3 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was reported that oil heated with soybean protein under reduced pressure, followed by fi ltration of the protein soy oil , accelerated gastrointestinal tract content transfer 2 . Furthermore, the content in the colon was actively excreted, ending up with remarkable weight-loss even though amounts ingested were constant 3 .…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that a soy oil-containing experimental diet fat-free AIN93G containing oil thermally processed with soybean protein followed by fi ltration inhibited body weight increases and increased fecal excretion without any adverse effects when given ad libitum to male Wistar rats for 12 weeks 3,13 . When thermal processing is conducted in the presence of air, in the preparation of weight-loss promoting oil, the contribution of oxidized polymers in the oil cannot be ignored in assessing its effects.…”
Section: Dicussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All the dieting oils, excluding Olestra ® , are subjected to hydrolysis and absorption in the small bowel; Olestra ® is not hydrolyzed by lipase, but excreted. The soy oil described above is a simple triacylglycerol, but probably contains a small amount of substances formed from components in soybean protein and oil during heating, and reduced body, liver and retroperitoneal fat tissue weights and serum TG levels in a 12-week animal experiment 12) . The oil did not result in deterioration of appetite but increased normal fecal excretion, leading to the assumption that there was reduced digestion and/or absorption of the diet.…”
Section: Introductionmentioning
confidence: 99%